N-Acetylcysteine prevents the decreases in cardiac collagen I/III ratio and systolic function in neonatal mice with prenatal alcohol exposure. (15th October 2019) - Ninh, Van K.; El Hajj, Elia C.; Ronis, Martin J.; Gardner, Jason D.
Highlights: Acute prenatal alcohol exposure decreased the collagen I/III ratio in the neonatal heart. Cardiac systolic function was diminished in alcohol-exposed neonates. N -Acetylcysteine prevented these cardiac changes in alcohol exposed neonates. Abstract: Prenatal alcohol exposure (PAE) is often associated with congenital heart defects, most commonly septal, valvular, and great vessel defects. However, there have been no known studies on whether PAE affects the resulting fibroblast population after development, and whether this has any consequences in the postnatal period. Our previous study focused on the effects of PAE on the postnatal fibroblast population, which translated into changes in cardiac extracellular matrix (ECM) composition and cardiac function in the neonatal heart. Moreover, our lab has previously demonstrated that alcohol-induced fibrosis is mediated by oxidative stress mechanisms in adult rat hearts following chronic alcohol exposure. Thus, we hypothesize that PAE alters cardiac ECM composition that persists into the postnatal period, leading to cardiac dysfunction, and these effects are prevented by antioxidant treatment. To investigate these effects, pregnant mice were intraperitoneally injected with 2.9 g EtOH/kg body weight on gestation days 6.75 and 7.25. Controls were injected with vehicle saline. Randomly selected dams in both groups were then treated with 100 mg/kg body weight of the antioxidant N -acetylcysteine (NAC) immediately after EtOH or vehicle administration. Left ventricular (LV) chamber dimension and function were assessed in sedated animals on neonatal day 5 using echocardiography. Ejection fraction decreased in the PAE group. NAC treatment prevented this depression of systolic function in PAE neonates. Hearts were analyzed for expression of fibroblast activation markers. Alpha smooth muscle actin (α-SMA) increased in PAE neonatal hearts, and this increase was prevented by NAC treatment. In PAE pups, collagen I decreased, but collagen III expression increased compared to saline animals; the overall collagen I/III ratio significantly decreased. When PAE mice were treated with NAC, collagen I/III ratio did not change. Overall, our data demonstrate that prenatal alcohol exposure produces changes in collagen subtype in neonatal cardiac ECM and a decline in systolic function, and these adverse effects were prevented by NAC treatment.